The immunogenic potential of AZD1402 (Elarekibep) T-cell epitopes in healthy volunteers and drug-exposed clinical trial participants - Liam Farrell; Stephanie M Bates; Alexander Walker; Monday Ogese; Xiaoli Meng; Sian Piper; John Mo; Katy Saide; Jorrit Hornberg; David Close; Ian Wallace; Catherine J Betts; et al. (Archives of Toxicology, 2026)
AZD1402 (Elarekibep) is a novel anticalin with engineered IL-4Rα antagonist binding properties that was under development for inhaled treatment of asthma. Structural similarity to tear-lipocalin is thought to limit immunogenicity risk; however, a range of treatment-emergent hypersensitivity-like adverse events were observed in a clinical study. This study aimed to (i) explore the activation of drug-exposed human T-cells with AZD1402- and tear lipocalin-derived peptides, (ii) characterise any T-cell epitopes contained within AZD1402 and (iii) define the nature of any response. Peripheral blood mononuclear cells (PBMC) from AZD1402-exposed study participants, alongside AZD1402-naïve donors, were cultured with AZD1402 and AZD1402-derived overlapping 18mer peptides. Proliferation and cytokine secretion were measured. T-cell clones were generated to characterise the diversity of T-cell epitopes and reactivity against equivalent tear-lipocalin peptides. AZD1402 contained multiple epitopes located in engineered “hotspot” regions of the molecule that activated PBMC and MHC class II-restricted CD4 + T-cell clones from both study participants and AZD1402-naïve donors. T-cell stimulatory peptides contained amino acid substitutions generated through mutagenesis to create AZD1402 target binding properties; similar T-cell epitopes were not found in tear-lipocalin. Detection of T-cell clones responsive towards AZD1402 and AZD1402-derived peptides provides evidence that immunogenic epitopes are formed naturally through processing of the AZD1402. These data describe a recall immunogenicity risk associated with AZD1402 and provide a framework by which to explore the immunogenic potential of modified sequences within anticalin or other large molecule therapeutics.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Fracture analysis of the lithium-bearing Cligga Head granite: Impacts on critical mineral mobilisation and fluid flow - Andrew J.M. Evans; Natalie J.C. Farrell; David A. Neave; Margaret E. Hartley; David Healy; John P. Waters; Tara R. McElhinney; Joshua J. Shea; Nico Bigaroni; Simon A. Hunt (Journal of Structural Geology, 2025)

The CALHM1 blocker CGP37157 increases seizure severity during status epilepticus in adult mice - Meghma Mitra; Amaya Sanz Rodriguez; Norman Delanty; Alan Beausang; Francesca M. Brett; Michael A. Farrell; Jane Cryan; Donncha F. O’Brien; David Henshall; Maria F. Cano-Abad; Tobias Engel (Purinergic Signalling, 2025)
Epilepsy is one of the most common chronic brain diseases affecting up to 70 million people worldwide. Major challenges of epilepsy treatment include the high pharmacoresistance in patients and the lack of disease-modification. Extracellular adenosine 3’triphosphate (ATP), a key neurotransmitter in the activation of the purinergic signalling system, is increasingly recognized to contribute to pathological brain hyperexcitability in epilepsy. Consequently, targeting ATP-release mechanisms may constitute a new therapeutic strategy for seizure control and epilepsy. The calcium channel, Calcium Homeostasis Modulator 1 (CALHM1), a voltage-gated, non-selective ion channel that permits the passage of various cations and small molecules, is expressed in neurons and plays an essential role during neuronal excitability and neurotransmission. In addition to ions, CALHM1 also allows the passage of ATP into the extracellular space, activating thereby purinergic receptors. Here, we tested if the pharmacological blocking of CALHM1 via CGP37157 (7-chloro-5-(2-chlorophenyl)-3,5-dihydro-4,1-benzothiazepin-2-(1H)-one) alters the severity of intra-amygdala kainic acid-induced status epilepticus. Our results show that CGP37157 increased the severity of seizures during status epilepticus. In addition, CALHM1 protein levels are down-regulated in the hippocampus in epileptic mice and Temporal Lobe Epilepsy (TLE) patients. In summary, our results identify CALHM1 as a new contributor to seizures and suggest targeting of CALHM1 as new treatment strategy for epilepsy.

Abundance Trends of Pacific Salmon During a Quarter Century of ESA Protection - Michael J. Ford; Steven T. Lindley; Katie A. Barnas; Andrew O. Shelton; Brian C. Spence; Laurie A. Weitkamp; Damon M. Holzer; David A. Boughton; Elizabeth E. Holmes; James M. Myers; Chris E. Jordan; Heidi Fish; et al. (Fish and Fisheries, 2025)
Between 1989 and 2007, 28 Distinct Population Segments (DPS) of Pacific salmon ( Oncorhynchus spp.) spawning in rivers in California and the Pacific Northwest (Oregon, Washington, Idaho) were listed (protected) under the US Endangered Species Act (ESA). In the roughly 25 years since then, considerable efforts have been made to recover these populations, but no DPS has increased sufficiently to be delisted. We evaluated abundance trends of ESA‐listed Pacific salmon DPS, along with DPS that were not ESA‐listed. Our goal was to evaluate whether protected DPS increased in abundance during the period of protection (nominally 1995–2020 in our study), either in absolute terms or relative to the unprotected DPS. A majority of the protected DPS had increasing abundance trends over this time period, and protected populations had higher median trends than non‐protected populations of the same species. Geographically, populations in the Pacific Northwest had higher median trends than those in California. Among species of protected populations, Chinook salmon ( O. tshawytscha ), chum salmon ( O. keta ) and sockeye salmon ( O. nerka ) had higher median trends than coho salmon ( O. kisutch ) and steelhead (anadromous O. mykiss ). For most DPS (listed and unlisted), trends in harvest rates and hatchery releases were relatively stable during the same time period, whereas trends in indicators related to freshwater and marine climate were generally negative for salmon. Our results suggest that salmon recovery actions may have helped to stabilise and increase protected DPS, but most remain far below their recovery goals.

Trophic transfer of per- and polyfluoroalkyl acids in a periphyton-mayfly-zebrafish food chain - Matthew R. Farrell; David B. Buchwalter; Rebecca A. Weed; Jeffrey R. Enders; Antonio Planchart (Aquatic Toxicology, 2025)

Revisiting the sustainability science research agenda - Mesfin Sahle; Shruti Ashish Lahoti; So-Young Lee; Katja Brundiers; Carena J. van Riper; Christian Pohl; Herlin Chien; Iris C. Bohnet; Noé Aguilar-Rivera; Peter Edwards; Prajal Pradhan; Tobias Plieninger; et al. (Sustainability Science, 2025)

Using Digital Twins of the Ocean to Build Capacity in the Wider Caribbean Region - Ali Hochberg; Lorna Inniss; Joana Akrofi; Kadean Blake-Smithen; David Farrell; Magali Goncalves; Rahanna Juman (Oceanography, 2025)
An emerging technology for building capacity to make decisions in the ocean space is the development of Digital Twins of the Ocean (DTOs). A DTO is a virtual replication of the ocean environment, including its properties, behaviors, and processes (https://www.​mercator-​ocean.eu/​en/​digital-​twin-ocean/). These digital replicas are created using a combination of real-time data collected from satellites and thousands of sensors deployed around the world, as well as outputs of advanced models and computer simulations.

Beyond Academia: A case for reviews of gray literature for science-policy processes and applied research - Yuki Yoshida; Nadia Sitas; Lelani Mannetti; Patrick O’Farrell; Gabriela Arroyo-Robles; Marta Berbés-Blázquez; David González-Jiménez; Valerie Nelson; Aidin Niamir; Zuzana V. Harmáčková (Environmental Science & Policy, 2024)

Iterative Development of an Interactive Website to Support Shared Decision-Making in Metastatic Breast Cancer - Claire C. Conley; Sophia Cumbo; Jacqueline Chavez Ochoa; Afton Boles; Jennifer D. Rodriguez; Nicole Schwab; David Farrell; Suzan Abduljawad; Claudine Isaacs; Suzanne C. O’Neill (Journal of Cancer Education, 2024)

Soil N 2 O emissions during dry fallow periods - Rémi Cardinael; Louise Barton; Marc Corbeels; Johan Six; David Rowlings; Armwell Shumba; Regis Chikowo; Mark Farrell (Global Change Biology, 2024)
Shang et al. (2024) recently suggested to include nitrous oxide (N 2 O) emissions during the fallow period to better estimate N 2 O emission factors (EFs). We however highlighted several pitfalls of the proposed adjusted EFs for croplands in the specific case of dry subhumid, semiarid, and arid regions with dry fallow periods, these regions covering about 47% of the Earth's terrestrial area.

A novel eDNA approach for rare species monitoring: Application of long-read shotgun sequencing to Lynx rufus soil pawprints - Samantha A. Koda; Mark McCauley; Jessica A. Farrell; Isabelle J. Duffy; Fiona G. Duffy; Sandra Loesgen; Jenny Whilde; David J. Duffy (Biological Conservation, 2023)

Spatial effort displacement in Florida commercial reef fisheries after red tides - Larry Perruso; Shay O'Farrell; David Chagaris; Iliana Chollett (Estuarine, Coastal and Shelf Science, 2023)

Designing healthier plant-based foods: Fortification, digestion, and bioavailability - Isobelle Farrell McClements; David Julian McClements (Food Research International, 2023)

A pilot study investigating feasibility of mainstreaming germline BRCA1 and BRCA2 testing in high-risk patients with breast and/or ovarian cancer in three tertiary Cancer Centres in Ireland - Terri Patricia McVeigh; Karl J. Sweeney; Donal J. Brennan; Una M. McVeigh; Simon Ward; Ann Strydom; Sheila Seal; Katherine Astbury; Paul Donnellan; Joanne Higgins; Maccon Keane; Michael J. Kerin; et al. (Familial Cancer, 2023)

Using Protection Motivation Theory to Predict Intentions for Breast Cancer Risk Management: Intervention Mechanisms from a Randomized Controlled Trial - Claire C. Conley; Karen J. Wernli; Sarah Knerr; Tengfei Li; Kathleen Leppig; Kelly Ehrlich; David Farrell; Hongyuan Gao; Erin J. A. Bowles; Amanda L. Graham; George Luta; Jinani Jayasekera; et al. (Journal of Cancer Education, 2023)
The purpose of this study is to evaluate the direct and indirect effects of a web-based, Protection Motivation Theory (PMT)–informed breast cancer education and decision support tool on intentions for risk-reducing medication and breast MRI among high-risk women. Women with ≥ 1.67% 5-year breast cancer risk ( N = 995) were randomized to (1) control or (2) the PMT-informed intervention. Six weeks post-intervention, 924 (93% retention) self-reported PMT constructs and behavioral intentions. Bootstrapped mediations evaluated the direct effect of the intervention on behavioral intentions and the mediating role of PMT constructs. There was no direct intervention effect on intentions for risk-reducing medication or MRI ( p ’s ≥ 0.12). There were significant indirect effects on risk-reducing medication intentions via perceived risk, self-efficacy, and response efficacy, and on MRI intentions via perceived risk and response efficacy ( p ’s ≤ 0.04). The PMT-informed intervention effected behavioral intentions via perceived breast cancer risk, self-efficacy, and response efficacy. Future research should extend these findings from intentions to behavior. ClinicalTrials.gov Identifier: NCT03029286 (date of registration: January 24, 2017).

A Web-based Lifestyle Intervention for Cancer Survivors: Feasibility and Acceptability of SurvivorSHINE - Victoria A. Williams; Nashira I. Brown; Roman Johnson; M. Cole Ainsworth; David Farrell; Margaux Barnes; Suzanne Perumean-Chaney; Kevin Fontaine; Michelle Y. Martin; Dori Pekmezi; Wendy Demark-Wahnefried (Journal of Cancer Education, 2022)

Carbon and climate implications of rewetting a raised bog in Ireland - David Wilson; Francis Mackin; Juha‐Pekka Tuovinen; Gerald Moser; Catherine Farrell; Florence Renou‐Wilson (Global Change Biology, 2022)
Peatland rewetting has been proposed as a vital climate change mitigation tool to reduce greenhouse gas emissions and to generate suitable conditions for the return of carbon (C) sequestration. In this study, we present annual C balances for a 5‐year period at a rewetted peatland in Ireland (rewetted at the start of the study) and compare the results with an adjacent drained area (represents business‐as‐usual). Hydrological modelling of the 230‐hectare site was carried out to determine the likely ecotopes (vegetation communities) that will develop post‐rewetting and was used to inform a radiative forcing modelling exercise to determine the climate impacts of rewetting this peatland under five high‐priority scenarios (SSP1‐1.9, SS1‐2.6, SSP2‐4.5, SSP3‐7.0 and SSP5‐8.5). The drained area (marginal ecotope) was a net C source throughout the study and emitted 157 ± 25.5 g C m −2 year −1 . In contrast, the rewetted area (sub‐central ecotope) was a net C sink of 78.0 ± 37.6 g C m −2 year −1 , despite relatively large annual methane emissions post‐rewetting (average 19.3 ± 5.2 g C m −2 year −1 ). Hydrological modelling predicted the development of three key ecotopes at the site, with the sub‐central ecotope predicted to cover 24% of the site, the sub‐marginal predicted to cover 59% and the marginal predicted to cover 16%. Using these areal estimates, our radiative forcing modelling projects that under the SSP1‐1.9 scenario, the site will have a warming effect on the climate until 2085 but will then have a strong cooling impact. In contrast, our modelling exercise shows that the site will never have a cooling impact under the SSP5‐8.5 scenario. Our results confirm the importance of rapid rewetting of drained peatland sites to (a) achieve strong C emissions reductions, (b) establish optimal conditions for C sequestration and (c) set the site on a climate cooling trajectory.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Host‐pathogen‐environment interactions predict survival outcomes of adult sockeye salmon ( Oncorhynchus nerka ) released from fisheries - Amy K. Teffer; Scott G. Hinch; Kristina M. Miller; David. A. Patterson; Arthur L. Bass; Steven J. Cooke; Anthony P. Farrell; Terry D. Beacham; Jacqueline M. Chapman; Francis Juanes (Molecular Ecology, 2022)
Incorporating host‐pathogen(s)‐environment axes into management and conservation planning is critical to preserving species in a warming climate. However, the role pathogens play in host stress resilience remains largely unexplored in wild animal populations. We experimentally characterized how independent and cumulative stressors (fisheries handling, high water temperature) and natural infections affected the health and longevity of released wild adult sockeye salmon ( Oncorhynchus nerka ) in British Columbia, Canada. Returning adults were collected before and after entering the Fraser River, yielding marine‐ and river‐collected groups, respectively ( N = 185). Fish were exposed to a mild (seine) or severe (gill net) fishery treatment at collection, and then held in flow‐through freshwater tanks for up to four weeks at historical (14°C) or projected migration temperatures (18°C). Using weekly nonlethal gill biopsies and high‐throughput qPCR, we quantified loads of up to 46 pathogens with host stress and immune gene expression. Marine‐collected fish had less severe infections than river‐collected fish, a short migration distance (100 km, 5–7 days) that produced profound infection differences. At 14°C, river‐collected fish survived 1–2 weeks less than marine‐collected fish. All fish held at 18°C died within 4 weeks unless they experienced minimal handling. Gene expression correlated with infections in river‐collected fish, while marine‐collected fish were more stressor‐responsive. Cumulative stressors were detrimental regardless of infections or collection location, probably due to extreme physiological disturbance. Because river‐derived infections correlated with single stressor responses, river entry probably decreases stressor resilience of adult salmon by altering both physiology and pathogen burdens, which redirect host responses toward disease resistance.

Kynurenic Acid Protects Against Reactive Glial-associated Reductions in the Complexity of Primary Cortical Neurons - Kate O’Reilly; Katherine O’Farrell; Oivind Midttun; Yuliia Rakovets; Jennifer David -Bercholz; Andrew Harkin (Journal of Neuroimmune Pharmacology, 2021)

Effects of global warming on fishes and fisheries - David J. McKenzie; Benjamin Geffroy; Anthony P. Farrell (Journal of Fish Biology, 2021)

Intraspecific variation in tolerance of warming in fishes - David J. McKenzie; Yangfan Zhang; Erika J. Eliason; Patricia M. Schulte; Guy Claireaux; Felipe R. Blasco; Julie J.H Nati; Anthony P. Farrell (Journal of Fish Biology, 2021)
Intraspecific variation in key traits such as tolerance of warming can have profound effects on ecological and evolutionary processes, notably responses to climate change. The empirical evidence for three primary elements of intraspecific variation in tolerance of warming in fishes is reviewed. The first is purely mechanistic that tolerance varies across life stages and as fishes become mature. The limited evidence indicates strongly that this is the case, possibly because of universal physiological principles. The second is intraspecific variation that is because of phenotypic plasticity, also a mechanistic phenomenon that buffers individuals’ sensitivity to negative impacts of global warming in their lifetime, or to some extent through epigenetic effects over successive generations. Although the evidence for plasticity in tolerance to warming is extensive, more work is required to understand underlying mechanisms and to reveal whether there are general patterns. The third element is intraspecific variation based on heritable genetic differences in tolerance, which underlies local adaptation and may define long‐term adaptability of a species in the face of ongoing global change. There is clear evidence of local adaptation and some evidence of heritability of tolerance to warming, but the knowledge base is limited with detailed information for only a few model or emblematic species. There is also strong evidence of structured variation in tolerance of warming within species, which may have ecological and evolutionary significance irrespective of whether it reflects plasticity or adaptation. Although the overwhelming consensus is that having broader intraspecific variation in tolerance should reduce species vulnerability to impacts of global warming, there are no sufficient data on fishes to provide insights into particular mechanisms by which this may occur.

Renewable cellulosic nanocomposites for food packaging to avoid fossil fuel plastic pollution: a review - Umair Qasim; Ahmed I. Osman; Ala’a H. Al-Muhtaseb; Charlie Farrell; Mohammed Al-Abri; Muzaffar Ali; Dai-Viet N. Vo; Farrukh Jamil; David W. Rooney (Environmental Chemistry Letters, 2021)
The extensive use of petroleum-based synthetic and non-biodegradable materials for packaging applications has caused severe environmental damage. The rising demand for sustainable packaging materials has encouraged scientists to explore abundant unconventional materials. For instance, cellulose, extracted from lignocellulosic biomass, has gained attention owing to its ecological and biodegradable nature. This article reviews the extraction of cellulose nanoparticles from conventional and non-conventional lignocellulosic biomass, and the preparation of cellulosic nanocomposites for food packaging. Cellulosic nanocomposites exhibit exceptional mechanical, biodegradation, optical and barrier properties, which are attributed to the nanoscale structure and the high specific surface area, of 533 m 2 g −1 , of cellulose. The mechanical properties of composites improve with the content of cellulose nanoparticles, yet an excessive amount induces agglomeration and, in turn, poor mechanical properties. Addition of cellulose nanoparticles increases tensile properties by about 42%. Barrier properties of the composites are reinforced by cellulose nanoparticles; for instance, the water vapor permeability decreased by 28% in the presence of 5 wt% cellulose nanoparticles. Moreover, 1 wt% addition of filler decreased the oxygen transmission rate by 21%. We also discuss the eco-design process, designing principles and challenges.

Advanced materials and technologies for supercapacitors used in energy conversion and storage: a review - M. I. A. Abdel Maksoud; Ramy Amer Fahim; Ahmed Esmail Shalan; M. Abd Elkodous; S. O. Olojede; Ahmed I. Osman; Charlie Farrell; Ala’a H. Al-Muhtaseb; A. S. Awed; A. H. Ashour; David W. Rooney (Environmental Chemistry Letters, 2021)
Supercapacitors are increasingly used for energy conversion and storage systems in sustainable nanotechnologies. Graphite is a conventional electrode utilized in Li-ion-based batteries, yet its specific capacitance of 372 mA h g −1 is not adequate for supercapacitor applications. Interest in supercapacitors is due to their high-energy capacity, storage for a shorter period and longer lifetime. This review compares the following materials used to fabricate supercapacitors: spinel ferrites, e.g., MFe 2 O 4 , MMoO 4 and MCo 2 O 4 where M denotes a transition metal ion; perovskite oxides; transition metals sulfides; carbon materials; and conducting polymers. The application window of perovskite can be controlled by cations in sublattice sites. Cations increase the specific capacitance because cations possess large orbital valence electrons which grow the oxygen vacancies. Electrodes made of transition metal sulfides, e.g., ZnCo 2 S 4 , display a high specific capacitance of 1269 F g −1 , which is four times higher than those of transition metals oxides, e.g., Zn–Co ferrite, of 296 F g −1 . This is explained by the low charge-transfer resistance and the high ion diffusion rate of transition metals sulfides. Composites made of magnetic oxides or transition metal sulfides with conducting polymers or carbon materials have the highest capacitance activity and cyclic stability. This is attributed to oxygen and sulfur active sites which foster electrolyte penetration during cycling, and, in turn, create new active sites.

Plastic Ingestion in Post-hatchling Sea Turtles: Assessing a Major Threat in Florida Near Shore Waters - Catherine B. Eastman; Jessica A. Farrell; Liam Whitmore; Devon R. Rollinson Ramia; Rachel S. Thomas; Jenifer Prine; Scott F. Eastman; Todd Z. Osborne; Mark Q. Martindale; David J. Duffy (Frontiers in Marine Science, 2020)

Horizon scanning for South African biodiversity: A need for social engagement as well as science - Colleen L. Seymour; Lindsey Gillson; Matthew F. Child; Krystal A. Tolley; Jock C. Curie; Jessica M. da Silva; Graham J. Alexander; Pippin Anderson; Colleen T. Downs; Benis N. Egoh; David A. Ehlers Smith; Yvette C. Ehlers Smith; et al. (Ambio, 2020)

Production and characterisation of activated carbon and carbon nanotubes from potato peel waste and their application in heavy metal removal. - Ahmed I. Osman; Jacob Blewitt; Jehad K. Abu-Dahrieh; Charlie Farrell; Ala’a H. Al-Muhtaseb; John Harrison; David W. Rooney (Environmental Science and Pollution Research, 2019)
Herein, activated carbon (AC) and carbon nanotubes (CNTs) were synthesised from potato peel waste (PPW). Different ACs were synthesised via two activation steps: firstly, with phosphoric acid (designated PP) and then using potassium hydroxide (designated PK). The AC produced after the two activation steps showed a surface area as high as 833 m 2 g −1 with a pore volume of 0.44 cm 3 g −1 , where the raw material of PPW showed a surface area < 4 m 2 g −1 . This can help aid and facilitate the concept of the circular economy by effectively up-cycling and valorising waste lignocellulosic biomass such as potato peel waste to high surface area AC and subsequently, multi-walled carbon nanotubes (MWCNTs). Consequently, MWCNTs were prepared from the produced AC by mixing it with the nitrogen-based material melamine and iron precursor, iron (III) oxalate hexahydrate. This produced hydrophilic multi-wall carbon nanotubes (MWCNTs) with a water contact angle of θ = 14.97 °. Both AC and CNT materials were used in heavy metal removal (HMR) where the maximum lead absorption was observed for sample PK with a 84% removal capacity after the first hour of testing. This result signifies that the synthesis of these up-cycled materials can have applications in areas such as wastewater treatment or other conventional AC/CNT end uses with a rapid cycle time in a two-fold approach to improve the eco-friendly synthesis of such value-added products and the circular economy from a significant waste stream, i.e., PPW.

Effects of plant functional group removal on structure and function of soil communities across contrasting ecosystems - Nicolas Fanin; Paul Kardol; Mark Farrell; Anne Kempel; Marcel Ciobanu; Marie‐Charlotte Nilsson; Michael J. Gundale; David A. Wardle (Ecology Letters, 2019)
Loss of plant diversity has an impact on ecosystems worldwide, but we lack a mechanistic understanding of how this loss may influence below‐ground biota and ecosystem functions across contrasting ecosystems in the long term. We used the longest running biodiversity manipulation experiment across contrasting ecosystems in existence to explore the below‐ground consequences of 19 years of plant functional group removals for each of 30 contrasting forested lake islands in northern Sweden. We found that, against expectations, the effects of plant removals on the communities of key groups of soil organisms (bacteria, fungi and nematodes), and organic matter quality and soil ecosystem functioning (decomposition and microbial activity) were relatively similar among islands that varied greatly in productivity and soil fertility. This highlights that, in contrast to what has been shown for plant productivity, plant biodiversity loss effects on below‐ground functions can be relatively insensitive to environmental context or variation among widely contrasting ecosystems.

RGD-decorated cholesterol stabilized polyplexes for targeted siRNA delivery to glioblastoma cells - Bo Lou; Kate Connor; Kieron Sweeney; Ian S. Miller; Alice O’Farrell; Eduardo Ruiz-Hernandez; David M. Murray; Garry P. Duffy; Alan Wolfe; Enrico Mastrobattista; Annette T. Byrne; Wim E. Hennink (Drug Delivery and Translational Research, 2019)

A multi-criterion approach for prioritizing areas in urban ecosystems for active restoration following invasive plant control - Elana Mostert; Mirijam Gaertner; Patricia M. Holmes; Patrick J. O’Farrell; David M. Richardson (Environmental Management, 2018)

Correction to: Managing Urban Plant Invasions: a Multi-Criteria Prioritization Approach - Luke J. Potgieter; Mirijam Gaertner; Ulrike M. Irlich; Patrick J. O’Farrell; Louise Stafford; Hannah Vogt; David M. Richardson (Environmental Management, 2018)

Managing Urban Plant Invasions: a Multi-Criteria Prioritization Approach - Luke J. Potgieter; Mirijam Gaertner; Ulrike M. Irlich; Patrick J. O’Farrell; Louise Stafford; Hannah Vogt; David M. Richardson (Environmental Management, 2018)

Alien plants as mediators of ecosystem services and disservices in urban systems: a global review - Luke J. Potgieter; Mirijam Gaertner; Christoph Kueffer; Brendon M. H. Larson; Stuart W. Livingstone; Patrick J. O’Farrell; David M. Richardson (Biological Invasions, 2017)

EUREC4A: A Field Campaign to Elucidate the Couplings Between Clouds, Convection and Circulation - Sandrine Bony; Bjorn Stevens; Felix Ament; Sebastien Bigorre; Patrick Chazette; Susanne Crewell; Julien Delanoë; Kerry Emanuel; David Farrell; Cyrille Flamant; Silke Gross; Lutz Hirsch; et al. (Surveys in Geophysics, 2017)
Trade-wind cumuli constitute the cloud type with the highest frequency of occurrence on Earth, and it has been shown that their sensitivity to changing environmental conditions will critically influence the magnitude and pace of future global warming. Research over the last decade has pointed out the importance of the interplay between clouds, convection and circulation in controling this sensitivity. Numerical models represent this interplay in diverse ways, which translates into different responses of trade-cumuli to climate perturbations. Climate models predict that the area covered by shallow cumuli at cloud base is very sensitive to changes in environmental conditions, while process models suggest the opposite. To understand and resolve this contradiction, we propose to organize a field campaign aimed at quantifying the physical properties of trade-cumuli (e.g., cloud fraction and water content) as a function of the large-scale environment. Beyond a better understanding of clouds-circulation coupling processes, the campaign will provide a reference data set that may be used as a benchmark for advancing the modelling and the satellite remote sensing of clouds and circulation. It will also be an opportunity for complementary investigations such as evaluating model convective parameterizations or studying the role of ocean mesoscale eddies in air–sea interactions and convective organization.

Highly variable male courtship behavioral sequences in a crambid moth - Shannon L. Farrell; David A. Andow (Journal of Ethology, 2017)

Multiyear greenhouse gas balances at a rewetted temperate peatland - David Wilson; Catherine A. Farrell; David Fallon; Gerald Moser; Christoph Müller; Florence Renou‐Wilson (Global Change Biology, 2016)
Drained peat soils are a significant source of greenhouse gas ( GHG ) emissions to the atmosphere. Rewetting these soils is considered an important climate change mitigation tool to reduce emissions and create suitable conditions for carbon sequestration. Long‐term monitoring is essential to capture interannual variations in GHG emissions and associated environmental variables and to reduce the uncertainty linked with GHG emission factor calculations. In this study, we present GHG balances: carbon dioxide ( CO 2 ), methane ( CH 4 ) and nitrous oxide (N 2 O) calculated for a 5‐year period at a rewetted industrial cutaway peatland in Ireland (rewetted 7 years prior to the start of the study); and compare the results with an adjacent drained area (2‐year data set), and with ten long‐term data sets from intact (i.e. undrained) peatlands in temperate and boreal regions. In the rewetted site, CO 2 exchange (or net ecosystem exchange ( NEE )) was strongly influenced by ecosystem respiration ( R eco ) rather than gross primary production ( GPP ). CH 4 emissions were related to soil temperature and either water table level or plant biomass. N 2 O emissions were not detected in either drained or rewetted sites. Rewetting reduced CO 2 emissions in unvegetated areas by approximately 50%. When upscaled to the ecosystem level, the emission factors (calculated as 5‐year mean of annual balances) for the rewetted site were (± SD ) −104 ± 80 g CO 2 ‐C m −2 yr −1 (i.e. CO 2 sink) and 9 ± 2 g CH 4 ‐C m −2 yr −1 (i.e. CH 4 source). Nearly a decade after rewetting, the GHG balance (100‐year global warming potential) had reduced noticeably (i.e. less warming) in comparison with the drained site but was still higher than comparative intact sites. Our results indicate that rewetted sites may be more sensitive to interannual changes in weather conditions than their more resilient intact counterparts and may switch from an annual CO 2 sink to a source if triggered by slightly drier conditions.

Aluminum toxicity risk reduction as a result of reduced acid deposition in Adirondack lakes and ponds - Toby M. Michelena; Jeremy L. Farrell; David A. Winkler; Christine A. Goodrich; Charles W. Boylen; James W. Sutherland; Sandra A. Nierzwicki-Bauer (Environmental Monitoring and Assessment, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Evidence for multiple sensory circuits in the brain arising from the respiratory system: an anterograde viral tract tracing study in rodents - Alice E. McGovern; Nicholas Davis-Poynter; Seung-Kwon Yang; David G. Simmons; Michael J. Farrell; Stuart B. Mazzone (Brain Structure and Function, 2015)

Mouse genome annotation by the RefSeq project - Kelly M. McGarvey; Tamara Goldfarb; Eric Cox; Catherine M. Farrell; Tripti Gupta; Vinita S. Joardar; Vamsi K. Kodali; Michael R. Murphy; Nuala A. O’Leary; Shashikant Pujar; Bhanu Rajput; Sanjida H. Rangwala; et al. (Mammalian Genome, 2015)
Complete and accurate annotation of the mouse genome is critical to the advancement of research conducted on this important model organism. The National Center for Biotechnology Information (NCBI) develops and maintains many useful resources to assist the mouse research community. In particular, the reference sequence (RefSeq) database provides high-quality annotation of multiple mouse genome assemblies using a combinatorial approach that leverages computation, manual curation, and collaboration. Implementation of this conservative and rigorous approach, which focuses on representation of only full-length and non-redundant data, produces high-quality annotation products. RefSeq records explicitly link sequences to current knowledge in a timely manner, updating public records regularly and rapidly in response to nomenclature updates, addition of new relevant publications, collaborator discussion, and user feedback. Whole genome re-annotation is also conducted at least every 12–18 months, and often more frequently in response to assembly updates or availability of informative data. This article highlights key features and advantages of RefSeq genome annotation products and presents an overview of NCBI processes to generate these data. Further discussion of NCBI’s resources highlights useful features and the best methods for accessing our data.

Environmental conditions and physiological state influence estuarine movements of homing sockeye salmon - S. Matthew Drenner; Scott G. Hinch; Eduardo G. Martins; Nathan B. Furey; Timothy D. Clark; Steven J. Cooke; David A. Patterson; David Robichaud; David W. Welch; Anthony P. Farrell; Richard E. Thomson (Fisheries Oceanography, 2015)
The reproductive migration of anadromous salmonids through estuarine waters is one of the most challenging stages of their life cycle, yet little is known about the environmental and physiological conditions that influence migratory behaviour. We captured, sampled tissues, tagged and released 365 sockeye salmon ( Oncorhynchus nerka ) homing through inner coastal waters towards the Fraser River, British Columbia, Canada. Biotelemetry was used to assess the behaviour of individual sockeye salmon approaching estuarine waters and at river entry, which were related to both fish physiological condition at release and to prevailing environmental conditions. Sockeye salmon tended to stay close to the shore, migrated during the day, and movements were related to tide. Sockeye salmon migration rate was linked to wind‐induced currents, salinity and an individual's physiological state, but these factors were specific to location and stock. We propose that wind‐induced currents exposed sockeye salmon entering the estuary to stronger olfactory cues associated with Fraser River water, which in turn resulted in faster migration rates presumably due to either an increased ability for olfactory navigation and/or advanced reproductive schedule through a neuroendocrine response to olfactory cues. However, once the migration had progressed further into more concentrated freshwater of the river plume, sockeye salmon presumably used wind‐induced currents to aid in movements towards the river, which may be associated with energy conservation. Results from this study improve our biological understanding of the movements of Fraser River sockeye salmon and are also broadly relevant to other anadromous salmonids homing in marine environments.

Modelling of fluid–solid interactions using an adaptive mesh fluid model coupled with a combined finite–discrete element model - Axelle Viré; Jiansheng Xiang; Frank Milthaler; Patrick Emmet Farrell; Matthew David Piggott; John-Paul Latham; Dimitrios Pavlidis; Christopher Charles Pain (Ocean Dynamics, 2012)

Clinical correlation and molecular evaluation confirm that the MLH1 p.Arg182Gly (c.544A>G) mutation is pathogenic and causes Lynch syndrome - Michael P. Farrell; David J. Hughes; Ian R. Berry; David J. Gallagher; Emily A. Glogowski; Stewart J. Payne; Michael J. Kennedy; Róisín M. Clarke; Susan A. White; Cian B. Muldoon; Fiona Macdonald; Pauline Rehal; et al. (Familial Cancer, 2012)

Isolation, characterization and predicted genome locations of ruff (Philomachus pugnax, AVES) microsatellite loci - Lindsay L. Farrell; Deborah A. Dawson; Gavin J. Horsburgh; Terry Burke; David B. Lank (Conservation Genetics Resources, 2012)

Breeding for Bio-ethanol Production in Lolium perenne L.: Association of Allelic Variation with High Water-Soluble Carbohydrate Content - Kerrie Farrar; David N. Bryant; Lesley Turner; Joe A. Gallagher; Ann Thomas; Markku Farrell; Mervyn O. Humphreys; Iain S. Donnison (BioEnergy Research, 2012)

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Experienced males have higher mating success than virgin males despite fitness costs to females - Panagiotis G. Milonas; Shannon L. Farrell; David A. Andow (Behavioral Ecology and Sociobiology, 2011)

Safeguarding Biodiversity and Ecosystem Services in the Little Karoo, South Africa - BENIS N. EGOH; BELINDA REYERS; JOSIE CARWARDINE; MICHAEL BODE; PATRICK J. O'FARRELL; KERRIE A. WILSON; HUGH P. POSSINGHAM; MATHIEU ROUGET; WILLEM De LANGE; DAVID M. RICHARDSON; RICHARD M. COWLING (Conservation Biology, 2010)
Global declines in biodiversity and the widespread degradation of ecosystem services have led to urgent calls to safeguard both. Responses to this urgency include calls to integrate the needs of ecosystem services and biodiversity into the design of conservation interventions. The benefits of such integration are purported to include improvements in the justification and resources available for these interventions. Nevertheless, additional costs and potential trade‐offs remain poorly understood in the design of interventions that seek to conserve biodiversity and ecosystem services. We sought to investigate the synergies and trade‐offs in safeguarding ecosystem services and biodiversity in South Africa's Little Karoo. We used data on three ecosystem services—carbon storage, water recharge, and fodder provision—and data on biodiversity to examine several conservation planning scenarios. First, we investigated the amount of each ecosystem service captured incidentally by a conservation plan to meet targets for biodiversity only while minimizing opportunity costs. We then examined the costs of adding targets for ecosystem services into this conservation plan. Finally, we explored trade‐offs between biodiversity and ecosystem service targets at a fixed cost. At least 30% of each ecosystem service was captured incidentally when all of biodiversity targets were met. By including data on ecosystem services, we increased the amount of services captured by at least 20% for all three services without additional costs. When biodiversity targets were reduced by 8%, an extra 40% of fodder provision and water recharge were obtained and 58% of carbon could be captured for the same cost. The opportunity cost (in terms of forgone production) of safeguarding 100% of the biodiversity targets was about US$500 million. Our results showed that with a small decrease in biodiversity target achievement, substantial gains for the conservation of ecosystem services can be achieved within our biodiversity priority areas for no extra cost.

An inverted seated posture decreases elbow flexion force and muscle activation - James Hearn; Farrell Cahill; David George Behm (European Journal of Applied Physiology, 2009)

Estimating the Effect of Protected Lands on the Development and Conservation of Their Surroundings - ROBERT I. McDONALD; CHRIS YUAN‐FARRELL; CHARLES FIEVET; MATTHIAS MOELLER; PETER KAREIVA; DAVID FOSTER; TED GRAGSON; ANN KINZIG; LAUREN KUBY; CHARLES REDMAN (Conservation Biology, 2007)
The fate of private lands is widely seen as key to the fate of biodiversity in much of the world. Organizations that work to protect biodiversity on private lands often hope that conservation actions on one piece of land will leverage the actions of surrounding landowners. Few researchers have, however, examined whether protected lands do in fact encourage land conservation nearby or how protected lands affect development in the surrounding landscape. Using spatiotemporal data sets on land cover and land protection for three sites (western North Carolina, central Massachusetts, and central Arizona), we examined whether the existence of a protected area correlates with an increased rate of nearby land conservation or a decreased rate of nearby land development. At all sites, newly protected conservation areas tended to cluster close to preexisting protected areas. This may imply that the geography of contemporary conservation actions is influenced by past decisions on land protection, often made for reasons far removed from concerns about biodiversity. On the other hand, we found no evidence that proximity to protected areas correlates with a reduced rate of nearby land development. Indeed, on two of our three sites the development rate was significantly greater in regions with more protected land. This suggests that each conservation action should be justified and valued largely for what is protected on the targeted land, without much hope of broader conservation leverage effects.

Behaviour and physiology of sockeye salmon homing through coastal waters to a natal river - Glenn T. Crossin; Scott G. Hinch; Steven J. Cooke; David W. Welch; Sonia D. Batten; David A. Patterson; Glen Van Der Kraak; J. Mark Shrimpton; Anthony P. Farrell (Marine Biology, 2007)

A high resolution green area index for modelling the seasonal dynamics of CO2 exchange in peatland vascular plant communities - David Wilson; Jukka Alm; Terhi Riutta; Jukka Laine; Kenneth A. Byrne; Edward P. Farrell; Eeva-Stiina Tuittila (Plant Ecology, 2007)

Somatic energy of sockeye salmon Oncorhynchus nerka at the onset of upriver migration: a comparison among ocean climate regimes - Glenn T. Crossin; Scott G. Hinch; Anthony P. Farrell; David A. Higgs; Michael C. Healey (Fisheries Oceanography, 2004)
We examined somatic energy patterns in two stocks (Chilko and Early Stuart) of adult Fraser River (British Columbia, Canada) sockeye salmon ( Oncorhynchus nerka ), collected at the end of their ocean residency, spanning years across different climate regimes. Both stocks had high levels of somatic energy in years with high open ocean productivity (1956, 1957, 2001 and 2002), and relatively low levels in years with poor open ocean productivity (1999 and 2000). For Early Stuart sockeye, energy levels in 1999 and 2000 were approximately 15% lower (∼1.5 MJ kg −1 ) than that in the 1950s, an amount of energy equivalent to that necessary for migrating 600 km upriver. In recent years (2001 and 2002), energy levels have increased by about 9% for both stocks. Low energy levels at the onset of upriver migration, particularly in years of energetically demanding in‐river conditions, such as high flows or temperatures, are likely to contribute to prespawning and en route mortality in Fraser sockeye.

Modulation of the chemical and biological properties of trans platinum complexes: monofunctional platinum complexes containing one nucleobase as potential antiviral chemotypes - David A. Sartori; Bernhard Miller; Ulrich Bierbach; N. Farrell (JBIC Journal of Biological Inorganic Chemistry, 2000)

Resonance mode analysis for volume estimation of asymmetric branching structures - David T. Raphael; M. A. Farrell Epstein (Annals of Biomedical Engineering, 1989)